PENENTUAN DAERAH PENANGKAPAN POTENSIAL IKAN TUNA MATA BESAR DENGAN MENGGUNAKAN CITRA SATELIT DI PERAIRAN LHOKSEUMAWE - Imam Shadiqin; Musri Musman; Alvi Rahmah (Universitas Syiah Kuala, 2016)
The study to determine a potential fishing ground of big-eye tuna using satellite images in the Lhokseumawe’s waters was conducted in February until April 2016 at Fish Landing Areas (TPI) located in the Pusong Village, Lhokseumawe City. Methods of data collection used in this study were obtained through the primary and secondary data. Determining the location of the catching by seeing the spread of chlorophyll-a in a processing map of satellite image and conducted the data collection of the catch in the field. Data were analyzed by analysis of chlorophyll-a and temperature, analysis of the relationship between chlorophyll-a, temperature, and the catching crop, the determination of potential areas of big-eye tuna, and mapping by using Arc Map and Seadas applications.The spread of chlorophyll-a in the waters of Lhokseumawe in February until April ranged between 0.012 mg m-3 to 0.566 mg m-3.The highest temperature in the waters of Lhokseumawe in February by an average was 29°C and the lowest temperature in March with an average temperature was 28°C. The lowest catching of big-eye tuna in February was an amount of 223.4 tons, the highest catching in March was an amount of 513.8 tons, and the catching in April was an amount of 317.5 tons. The potential fishing ground in February was located at coordinates 96°17'30''E–5°14'30''N and the potentialfishing ground was located at coordinates 96°42'30''E–6°24'30''N. In March, the potentialfishing ground was located at coordinates 96°21'30''E–5°43'30''N and the potentialfishing ground was located at coordinates 95°23'30''E–6°33'30''N. The position of potentialfishing groundin April was located at coordinates 96°31'30'' E– 5°43'30'' N. Penelitian penentuan daerah penangkapan potensial ikan tuna mata besar dengan menggunakan citra satelit di perairan Lhokseumawe telah dilakukan pada bulan Februari sampai April 2016 di Tempat Pendaratan Ikan (TPI) yang berada di Desa Pusong Kota Lhokseumawe. Metode pengumpulan data yang digunakan dengan memperoleh data primer (mengikuti langsung operasi penangkapan) dan data sekunder (data dari dinas terkait). Metode analisis data menggunakan analisis klorofil-a dan suhu, hubungan antara klorofil-a, suhu, dan hasil tangkapan, penentuan daerah potensial ikan tuna mata besar, dan pemetaan menggunakan aplikasi Arc map dan Seadas.Penyebaran kandungan klorofil-a di Perairan Lhokseumawe pada bulan Februari sampai April berkisar antara 0,012 mg m-3 sampai 0,566 mg m-3. Suhu di Perairan Lhokseumawe tertinggi pada bulan Februari dengan rata-rata 29°C dan suhu terendah pada bulan Maret dengan suhu rata-rata 28°C. Hasil tangkapan ikan tuna mata besar terendah pada bulan Februari sebesar 223,4 ton, hasil tangkapan tertinggi pada bulan Maret sebesar 513,8 ton, dan hasil tangkapan pada bulan April sebesar 317,5 ton. DPI potensial pada bulan Februari terletak di koordinat 96°17' BT dan 5°14' LU dan DPI kurang potensial terletak di koordinat 96°42' BT dan 6,01°24' LU. Pada bulan Maret DPI potensial terletak di koordinat96°21' BT dan 5°43' LU dan DPI kurang potensial terletak di koordinat 95°23' BT dan 6°33' LU. Posisi DPI potensial pada bulan April terletak dikoordinat96°31' BT dan 5°43' LU.